2008
DOI: 10.1183/09031936.00107507
|View full text |Cite
|
Sign up to set email alerts
|

High levels of Epstein–Barr virus in COPD

Abstract: Latent viral infection has been implicated in the pathophysiology of chronic obstructive pulmonary disease (COPD). Epstein-Barr virus (EBV) is known to be important in pulmonary fibrosis. The current authors hypothesised that EBV is associated with the pathogenesis of COPD.Sputum samples were collected from patients both during exacerbations of COPD and when stable. A control group of smokers who did not have airways obstruction also had their sputum examined. The presence of EBV DNA was established and quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 23 publications
3
41
0
Order By: Relevance
“…In one large cross sectional study with 18.883 participants, this association was stronger in COPD patients [33] (Table 1). Ebstein Barr virus infection, which is often found in COPD patients, is also associated with low levels of vitamin D [98,99]. Liou et al reported a relation between Toll-like receptors, external triggers and vitamin D-mediated innate immunity, and suggested that differences in the ability of human populations to produce vitamin D may contribute to susceptibility to microbial infections [100].…”
Section: Resultsmentioning
confidence: 99%
“…In one large cross sectional study with 18.883 participants, this association was stronger in COPD patients [33] (Table 1). Ebstein Barr virus infection, which is often found in COPD patients, is also associated with low levels of vitamin D [98,99]. Liou et al reported a relation between Toll-like receptors, external triggers and vitamin D-mediated innate immunity, and suggested that differences in the ability of human populations to produce vitamin D may contribute to susceptibility to microbial infections [100].…”
Section: Resultsmentioning
confidence: 99%
“…Some articles referred to other papers for methodological information and in these cases the index reference was studied. A few articles used the same population for detection of different viruses and it was assumed that data from the first published articles could be extrapolated to the latest published article [9][10][11].…”
Section: Data Collection Processmentioning
confidence: 99%
“…Respiratory viral infection accounts for approximately 40–60% of all acute exacerbation of COPD and up to 80% of asthma exacerbations, 5,118 and influenza virus is one of the infectious viruses commonly detected during acute exacerbation 11,12 . Influenza infection accounts for approximately 16–25% of all virus‐induced acute COPD exacerbation 7,119,120 .…”
Section: Influenza and Chronic Respiratory Diseasementioning
confidence: 99%